Gaple Gambling Practice in Community Celebrations Perspective of Customary Law and Criminal Law - Gunawan Hadi Purwanto; Muhammad Yasir; Mida Izalia (JURNAL AKTA, 2026)
Article 18B paragraph (2) of the 1945 Constitution states that the state recognizes and respects the unity of customary law communities and their traditional rights as long as they are alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia. Trucuk Village, Bojonegoro Regency, has a tradition of practicing gaple gambling during community celebrations. This study uses socio-legal research methods with historical and comparative approaches, and prescient analysis. The urgency of the discussion is that criminal law regulates that whatever form and method is used by the community in the practice of gambling is a criminal act. Based on local wisdom, the practice of gambling during community celebrations is a community activity that has been passed down from generation to generation. There is no criminal act, so the police cannot make arrests or criminal proceedings against the community. Laws and laws that live in the community (living law) have the same position as the source of national law. The state, through law enforcement apparatus, cannot directly arrest or dissolve the practice of gaple because it is a concrete form of the existence of community culture that is legally protected.